The foreign correspondent a novel - Furst, Alan
The Foreign Correspondent is the story of a handful of antifascists: the army officer known as "Colonel Ferrara," who fights for a lost cause in Spain; Arturo Salamone, the shrewd leader of a resistance group in Paris; and Christa von Schirren, the woman who becomes the love of Weisz's life, herself involved in a doomed resistance underground in Berlin.